A rare case of abdominal lymphangioma masquerading an adenaxal mass - Agarwal, Mukta; Bhushan, Divendu; Singh, Prashant; Bhadani, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Lymphangioma is an uncommon benign tumour of the lymphatic system. It can be localized (spleen, liver or thorax) or generalized. An abdominal location is exceptional (5%) and majority of cases occur in early childhood and it rarely presents in adulthood. Retroperitoneal lymphangioma account for less than 1% of all lymphangiomas here we present a rare case of retroperitoneal lymphangioma and patient presented as adenaxal mass.